Investigation and comparison of Turkish and American preschool teacher candidates' attitudes towards inclusion of young children with disabilities. Issue 11 (1st November 2016) - Rakap, Salih; Parlak-Rakap, Asiye; Aydin, Burak
ABSTRACT: Inclusion of young children with disabilities into general education classrooms is a common practice that has been implemented for many years in developed countries around the world and many developing countries have been creating and implementing laws and regulations to support inclusive education in early years. Although extant literature includes a commonly agreed definition for inclusion, the implementation of inclusive practices varies across countries. A critical factor for successful implementation of inclusive practices is teachers' attitudes towards inclusion of children with disabilities. The purpose of this study was to compare Turkish and American pre-service preschool teachers' attitudes towards inclusion of young children with disabilities and their willingness to work with children with severe behavioural, physical, and cognitive disabilities. A total of 123 pre-service teachers participated in the study. The results showed that pre-service teachers across two countries had similar attitudes towards inclusion and their attitudes were positive. Additionally, both groups of pre-service teachers reported more favourable attitudes towards working with children with severe physical disabilities than those who have severe cognitive and behavioural disabilities. Implications for future research and practices are discussed.